2020
DOI: 10.1093/ntr/ntaa084
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Cannabinoid and Nicotine Exposure Differentially Alters Adult Nicotine Self-Administration in Males and Females

Abstract: Introduction During adolescence, exposure to nicotine or cannabis independently induces effects on neuromaturation and later cognitive function. However, the potential effect of both drugs under co-use conditions has become of increasing concern given the prevalence of e-cigarettes, legalization of cannabis, and availability of synthetic “spice” cannabinoid agonists. Aims and Methods The current studies investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Moreover, THC exposure did not alter relapse to nicotine seeking induced by stress or nicotine-associated cues [ 182 ]. Another study found an increase in nicotine self-administration behavior in adult males at the lower rewarding nicotine dose following adolescent cannabinoid agonist exposure [ 183 ]. The reason for discrepancies in the findings of these studies may result from the different cannabinoid agonists used (THC versus synthetic WIN55,212).…”
Section: Effects Of Cannabinoid Exposure On Nicotine Addictive Propertiesmentioning
confidence: 99%
“…Moreover, THC exposure did not alter relapse to nicotine seeking induced by stress or nicotine-associated cues [ 182 ]. Another study found an increase in nicotine self-administration behavior in adult males at the lower rewarding nicotine dose following adolescent cannabinoid agonist exposure [ 183 ]. The reason for discrepancies in the findings of these studies may result from the different cannabinoid agonists used (THC versus synthetic WIN55,212).…”
Section: Effects Of Cannabinoid Exposure On Nicotine Addictive Propertiesmentioning
confidence: 99%
“…frontal gyrus significantly correlated with the reduced RT for the 3-back task for the r-cig condition only (Ernst et al, 2001b;Lawrence et al, 2002;Xu et al, 2005). Alternatively, ROIs such as the dorsolateral prefrontal cortex and hippocampus in the mesocortical pathway (Zakiniaeiz et al, 2019;Dukes et al, 2020) may also be involved. Thus, the association between the neuronal activations of these candidate ROIs and working memory performance can be investigated.…”
Section: Discussionmentioning
confidence: 96%
“…The lack of difference when the vapor concentration was increased to 60 mg/mL in the PG is perhaps unexpected but the dose-effect curves for intravenous self-administration of nicotine can be quite flat, e.g., across 2-to 3-fold differences in dose. For example, female mice self-administered similar intravenous infusions of nicotine whether it was 0.3 or 0.1 mg/kg/infusion (Dukes et al, 2020) and male rats self-administered similar numbers of intravenous infusions of 0.03 or 0.06 mg/kg/infusion nicotine (O’Dell et al, 2007). It is therefore most likely that the 30 mg/mL and 60 mg/mL conditions used here did not produce a large enough effective difference in delivered dose.…”
Section: Discussionmentioning
confidence: 99%